The influence of local economic conditions on start-ups and local open innovation system - Izabela Jonek-Kowalska; Radosław Wolniak (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The development of start-ups is a driving force of the local and regional economy. Therefore, it should be in the interest of municipal authorities to take actions for their organizational and resource support. In the conditions of limited public resources, however, it is a difficult and multifaceted task. Therefore, in this article, the authors attempt to determine the influence of local conditions on the establishment of start-ups. As a natural environment for the development of this type of entrepreneurship, cities were considered in which accessibility to infrastructure and human resources is high, and thus, by definition, conducive to creativity and innovation. Such a formulations of the objective and scope of the research allowed the existing theoretical and research gaps to be filled, relating to the identification and establishment of a hierarchy of local determinants of creating start-ups in the urban environment. The research in question was carried out on a representative sample of 287 Polish cities using questionnaire techniques and structural modelling. The results confirm the dominant influence of human and financial capital on the establishment of start-ups. The research also shows a slightly less significant influence of business incubators and technology parks on the creation of start-ups, which implies the need to improve the performance of these entities. The results also point to the positive role of direct city involvement in the development of this form of entrepreneurship.
Keywords: 650; city; innovation and entrepreneurship in the city; start-ups; urban economics and management